Current status of validation for robotic surgery simulators – a systematic review - Abboudi, Hamid; Khan, Mohammed S.; Aboumarzouk, Omar; Guru, Khurshid A.; Challacombe, Ben; Dasgupta, Prokar; Ahmed, Kamran (BJU international, 2013)
What's known on the subject? and What does the study add? Little is known on how best to train the future generation of robotic surgeons. It has been postulated that virtual reality (VR) simulators may aid the progression along the learning curve for this rapidly developing surgical technique within a safe training environment. There are several simulators available on the market, the best known is that developed by Intuitive Surgical Inc. The present study provides the first systematic review of all the trails of the various VR robotic platforms. It explores the evidence supporting the effectiveness of the various platforms for feasibility, reliability, validity, acceptability, educational impact and cost‐effectiveness. This article also highlights the deficiencies and future work required to advance robotic surgical training. To analyse studies validating the effectiveness of robotic surgery simulators. The MEDLINE®, EMBASE® and PsycINFO® databases were systematically searched until September 2011. References from retrieved articles were reviewed to broaden the search. The simulator name, training tasks, participant level, training duration and evaluation scoring were extracted from each study. We also extracted data on feasibility, validity, cost‐effectiveness, reliability and educational impact. We identified 19 studies investigating simulation options in robotic surgery. There are five different robotic surgery simulation platforms available on the market. In all, 11 studies sought opinion and compared performance between two different groups; ‘expert’ and ‘novice’. Experts ranged in experience from 21–2200 robotic cases. The novice groups consisted of participants with no prior experience on a robotic platform and were often medical students or junior doctors. The Mimic dV‐Trainer®, ProMIS®, SimSurgery Educational Platform® (SEP) and Intuitive systems have shown face, content and construct validity. The Robotic Surgical SimulatorTM system has only been face and content validated. All of the simulators except SEP have shown educational impact. Feasibility and cost‐effectiveness of simulation systems was not evaluated in any trial. Virtual reality simulators were shown to be effective training tools for junior trainees. Simulation training holds the greatest potential to be used as an adjunct to traditional training methods to equip the next generation of robotic surgeons with the skills required to operate safely. However, current simulation models have only been validated in small studies. There is no evidence to suggest one type of simulator provides more effective training than any other. More research is needed to validate simulated environments further and investigate the effectiveness of animal and cadaveric training in robotic surgery.